TINJAUAN KETIDAKHARMONISAN DALAM HUBUNGAN KELUARGA TERHADAP NUSYUZ ISTRI: PERSPEKTIF SOSIOLOGI DAN ANTROPOLOGI - Naufal (Islamic Family Law, STAI Sangatta Kutai Timur, 2026)
Marital disharmony remains a recurring issue in family life and often develops into more complex relational problems, including wives’ nusyuz. This study examines the factors underlying marital disharmony that lead to wives’ nusyuz in Mudalrejo Village, Loano District, Purworejo Regency. It adopts a descriptive qualitative design with a field research approach. Data analysis follows the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing. Primary data were obtained through interviews with community leaders, village officials, and family members, while secondary data were derived from relevant documents and literature. The findings reveal that disharmony is mainly caused by inadequate communication, husbands’ infidelity, and economic difficulties that generate wives’ dissatisfaction. Persistent unresolved conflicts often result in wives leaving their husbands and returning to their parental homes. Overall, marital disharmony emerges as the principal factor contributing to wives’ nusyuz, highlighting the importance of strengthening spousal communication to improve marital relationships.